Extended analysis of the Kr V spectrum - Rezende, D. C. J. (2010)
The spectrum of four-times-ionized krypton (Kr V) has been observed in the 230–4900 A˚ wavelength range, resulting in 91 new classified lines. We were able to identify 21 new energy levels belonging to the 4s2 4p5d, 4s2 4p5s, 4s2 4p6s, 4s2 4p5p and 4s4p2 4d configurations. Relativistic Hartree–Fock calculations were used to predict energy levels and transitions.